The girl who threw butterflies - Cochrane, Mick. (New York Alfred A. Knopf, 2009)
Eighth-grader Molly's ability to throw a knuckleball earns her a spot on the baseball team, which not only helps her feel connected to her recently deceased father, who loved baseball, it helps in other aspects of her life, as well.
Keywords: Baseball -- Fiction; Pitchers (Baseball) -- Fiction; Sex role -- Fiction; Grief -- Fiction; Mothers and daughters -- Fiction; Friendship -- Fiction; Buffalo (N.Y.) -- Fiction